Study on local plants as source of inhibitors to human glutathione s-transferase π (GST-P) / Phang Wai Mei - Phang, Wai Mei (2013)

(untitled)
The detoxification function of glutathione S-transferase π (GST-P) was associated with drug resistance in many cancers and become a major reason of chemotherapy failure and disease recurrence. Thus, inhibitors of GST-P were targeted in order to counteract the phenomenon of multidrug resistance. Ethanolic extracts of 43 local plant samples were screened for their inhibitory effect on GST-P activity. Among these, 30 ethanolic extracts displayed inhibition activity on GST-P and 13 out of the 30 ethanolic extracts have inhibition effects higher than 50%. Furthermore, Garcinia atroviridis (branch) and Leptospermum flavescens (leaf) ethanolic extracts have the highest inhibitory effect with a 100% inhibition on GST-P activity. These 13 ethanolic extracts were then subjected for IC50 determination, kinetic studies and cytotoxicity assays. Based on the IC50 value, the most active sample was Cinnamomum zeylanicum (branch) ethanolic extract with lowest IC50 value of 0.07 mg/mL, followed by Leptospermum flavescens (leaf) and Hibiscus tiliaceus (leaf) ethanolic extracts with IC50 values of 0.09 and 0.10 mg/mL respectively. 10 of the selected ethanolic extracts shown mixed mode inhibition on GST-P while the other 3 shown uncompetitive inhibitions. All of the 13 ethanolic extracts were not cytotoxic to both HT-29 and MRC-5 cell lines when tested alone, with IC50 value >100 μg/mL. Combination studies indicated that GST-P inhibition able to potentiate the cytotoxicity of doxorubicin hydrochloride on HT-29 cells, but not for cisplatin. Combination of doxorubicin hydrochloride-Cinnamomum zeylanicum (branch) ethanolic extract has the lowest IC50 value with IC50= 0.22 μg/mL. Nevertheless, Andrographis paniculata (leaf) and Lawsonia inermis (branch) ethanolic extracts incredibly increased the cytotoxicity of cisplatin on HT-29 cells with IC50 values of 4.70 and 5.46 μg/mL respectively. Bioassay-guided fractionation of Leptospermum flavescens (leaf) ethanolic extract on polyamide column resulted in a fraction with 95% inhibition on GST-P activity (50% methanol 2% acetic iv acid eluate). The fraction inhibited GST-P in mixed mode with IC50 value of 0.19 mg/mL. This fraction was not toxic to either HT-29 or MRC-5 cells. Combination of doxorubicin hydrochloride with the 50% methanol 2% acetic acid fraction of L. flavescens (leaf) ethanolic extract enhanced doxorubicin hydrochloride cytotoxicity on HT-29 cells with IC50= 0.26 μg/mL whereas combination of cisplatin-50% methanol 2% acetic acid fraction of L. flavescens (leaf) ethanolic extract gave an IC50 value of 8.38 μg/mL on cytotoxicity of HT-29 cells. Our results revealed that local plants can be source of GST-P inhibitors to enhance cytotoxicity of anticancer drugs.